Ewing's Sarcoma: Development of RNA Interference-Based Therapy for Advanced Disease. (11th March 2012) - Simmons, Olivia; Maples, Phillip B.; Senzer, Neil; Nemunaitis, John
Abstract : Ewing's sarcoma tumors are associated with chromosomal translocation between the EWS gene and the ETS transcription factor gene. These unique target sequences provide opportunity for RNA interference(i)-based therapy. A summary of RNAi mechanism and therapeutically designed products including siRNA, shRNA and bi-shRNA are described. Comparison is made between each of these approaches. Systemic RNAi-based therapy, however, requires protected delivery to the Ewing's sarcoma tumor site for activity. Delivery systems which have been most effective in preclinical and clinical testing are reviewed, followed by preclinical assessment of various silencing strategies with demonstration of effectiveness to EWS/FLI-1 target sequences. It is concluded that RNAi-based therapeutics may have testable and achievable activity in management of Ewing's sarcoma.